Social Media Use and Perceived Social Capital Dimensions among Students of Covenant University, Ota, Ogun State, Nigeria - Titilope, Afolayan Oluyinka; Muritala, Falade Adesola (University of Dar es Salaam Library Journal, 2023)
In this 21st century, social media plays a pivotal role in the lives of users due to innumerable benefits gained from its continuous usage, one of which is social capital. This study investigated social media use and perceived social capital dimensions among students at Covenant University, Ota, Ogun State. A survey design approach was adopted, using a structured and validated questionnaire to collect data. A total of 325 students served as the sample size, based on stratified sampling selection of 8 departments under the College of Science and Technology (CST) in Covenant University, Ota, Ogun State, Nigeria; while the Purposive sampling technique was used in the distribution of a questionnaire to students in the study area. Findings revealed a positive correlation between social media use of some popular sites such as Facebook. Instagram, LinkedIn, WeChat, Snapchat, and perceived online bonding as well as bridging capital. However, there were no significant differences between male and female students in their perceived online bonding and bridging social capital. In terms of relative contribution, Facebook had the strongest contribution to online bonding capital; while Instagram had the strongest contribution to bridging capital. It was concluded that the intense use of some popular social media sites drives the accumulation of bonding and bridging social capital. Therefore, based on the findings of this study, it was recommended that University management of Higher Education Institutions (HEIs) should create an enabling environment for the adoption and use of popular social media platforms by students, for quicker accessibility, faster formation and accumulation of bonding, and bridging social capital.